Pulmonary embolism in congenital bleeding disorders: intriguing discrepancies among different clotting factors deficiencies. Issue 5 (July 2016) - Girolami, Antonio; Cosi, Elisabetta; Tasinato, Valentina; Peroni, Edoardo; Girolami, Bruno; Lombardi, Anna Maria
Abstract : Pulmonary embolism is a complication of deep vein thrombosis. It occurs in the population with a normal clotting mechanism, but it may also occur in patients with congenital bleeding conditions. Here, we report on all cases of pulmonary embolism in congenital hemorrhagic disorders. All reported cases of pulmonary embolism in congenital coagulation disorders have been gathered by a time-unlimited PubMed search. Cross-checking of the references listed at the end of the single papers was carried out to avoid omissions. Seventy-two patients had an objectively demonstrated pulmonary embolism. The event occurred in patients with fibrinogen, factor V, factor VIII (FVII), FVIII, FIX, and FXI deficiency, and in those with von Willebrand's disease. No embolism was reported in FII, factor X, and FXIII deficiency. Thirty were women and 28 were men, whereas in the remaining 14 cases, sex was not reported. Age varied from 6 to 81 years (mean age 34.3 years). The management varied from only supportive to the administration of unfractionated heparin, low-molecular-weight heparin, and anti-vitamin K medications, accompanied by adequate replacement therapy. Evolution was fair or good in the majority of cases, but there were 10 fatalities. Risk factors were present in 61 patients. The most frequent of these were replacement therapy (35 cases), surgery (34), and old age (13). Some patients had more than one risk factor. Eleven patients had no risk factors. There are discrepancies in the prevalence of pulmonary embolism among different clotting disorders. The conditions most frequently affected are FVII deficiency and fibrinogen defects. The significance of the findings is discussed.